2009
DOI: 10.1002/hec.1485
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic versus static models in cost‐effectiveness analyses of anti‐viral drug therapy to mitigate an influenza pandemic

Abstract: Conventional (static) models used in health economics implicitly assume that the probability of disease exposure is constant over time and unaffected by interventions. For transmissible infectious diseases this is not realistic and another class of models is required, so-called dynamic models. This study aims to examine the differences between one dynamic and one static model, estimating the effects of therapeutic treatment with antiviral (AV) drugs during an influenza pandemic in the Netherlands. Specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 45 publications
1
69
0
2
Order By: Relevance
“…It is also important to note that the model used within the analysis is static rather than dynamic, assuming that infectivity is constant over time and unaffected by the interventions. Previous studies on other infectious diseases have found robust results using both static and dynamic models (see, for example, the study by Lugnér and colleagues 228 ). However, as Lugnér and colleagues point out, although their two models both showed the intervention to be cost-effective, they did produce differing cost-effectiveness ratios and outcomes may differ depending on the cost-effectiveness threshold.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is also important to note that the model used within the analysis is static rather than dynamic, assuming that infectivity is constant over time and unaffected by the interventions. Previous studies on other infectious diseases have found robust results using both static and dynamic models (see, for example, the study by Lugnér and colleagues 228 ). However, as Lugnér and colleagues point out, although their two models both showed the intervention to be cost-effective, they did produce differing cost-effectiveness ratios and outcomes may differ depending on the cost-effectiveness threshold.…”
Section: Discussionmentioning
confidence: 88%
“…For example, within the UK the highest rates of HIV infection are reported in men who have sex with men (47 per 1000) and in the black African community (37 per 1000). 179 Interestingly, Lugnér and colleagues 228 found their dynamic model to be far more sensitive than their static model to infection attack rates, thus creating large uncertainty about future attack rates. Although their findings may be context specific, it is an area for consideration when modelling HIV prevention given the increasing use of antiretroviral therapy (in the UK 87% of people receiving care were virally suppressed and unlikely to be infectious) and the ongoing development of treatments such as the antiretroviral combination drug Truvada and the role of pre-exposure prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…The cost-effectiveness of HPV vaccination in addition to screening Review informahealthcare.com consequently no room for herd immunity benefits exists nor can be expected [51].…”
Section: Discussion and Limitationmentioning
confidence: 99%
“…We note the great impact of that one article on other papers included it in this review, either directly [14,17] or indirectly [15,[18][19][20]. The articles were evaluated and compared on various issues, including type of modeling and specific values for health-economic input variables.…”
Section: Resultsmentioning
confidence: 99%
“…Article abstracts were read and evaluated on their appropriateness for the review, and 16 articles were read in total. Of these, 12 articles were judged to adhere to the aforementioned inclusion criteria [14][15][16][17][18][19][20][21][22][23][24][25] and four were discarded from this review [26][27][28][29]. With one exception ( [22]), all reviewed articles were published in 2004 or later.…”
Section: Methodsmentioning
confidence: 99%